Sucker Rod Pump Design using Petroleum Engineering Application– PEARL 4.0 as a Breakthrough Solution in Digitalization (Study Case PWP-13) at Limau Field, Pertamina Hulu Rokan, South Sumatra, Indonesia - Putra, Panca Wibawa; Suranto, Suranto; Kristanto, Dedi (Journal of Petroleum and Geothermal Technology, 2025)
PT. Pertamina Limau Field in South Sumatra, producing 4,113 BOPD and 10.69 MMSCFD from 11 structures, have a significant low production issue with well PWP-13. Although the well produces 40 BOPD, frequent failures in the sucker rod pump (SRP) system cause excessive downtime and low production, reaching 4,505 barrels oil (BO) in 2023. This research aimed to optimize PWP-13 production by redesigning the SRP system, applying API RP 11 L standards to improve the pump’s reliability. Build new calculation, The Petroleum Engineering Application (PEARL 4.0) integrated variables such as taper rod arrangement and sucker rod type. This PEARL 4.0 was then applied to well PWP-13 with Rig Service. Monitoring results indicated a production increase to 90 BOPD, with average incremental production reaching 60 BOPD, supported by extended operational lifetime. Financial analysis showed a high net present value (NPV) of 693 MUSD, internal rate of return (IRR) of 498%, and a payback period (POT) of 0.189 years, confirming a rapid return on investment (ROI) 8.6. The SRP redesign offers a sustainable solution for sucker rod failures, enhancing production efficiency and profitability for company. Keywords: artificial lift, sucker rod pump design, petroleum engineering application